The Influence of Pedagogic And Professional Competence of Ismuba Teachers On The Installation of Islamic Values In Students of Muhammadiyah Al Mujahidin Gunungkidul Junior High Schoool - Syadana Hanifah Endrairani; Arif Rahman; Hanif Cahyo Adi Kistoro (Linguanusa : Social Humanities, Education and Linguistic, 2024)
Background: Instilling Islamic religious values to students is not only a process of transfer of knowledge but also a process of transfer of value. In this process, the one who plays an active role in carrying out learning activities is a teacher. For this reason, teachers are required to have good competence and ability in teaching so that they can carry out their roles optimally. In this regard, teacher competencies that are directly related to the learning process are pedagogical competence and professional competence. Purpose: The purpose of this study is to determine how much contribution the pedagogical and professional competence of ISMUBA teachers has in influencing the instillation of Islamic religious values in students of SMP Muhammadiyah Al Mujahidin Gunungkidul. Design/methods/approach: The type of research conducted by the author is field research with a quantitative approach method based on post-positivistic philosophy. The population of the study used were 95 students of class VIII of SMP Muhammadiyah Al Mujahidin Gunungkidul. Data collection techniques in this study used questionnaires, interviews, observations and documentation. While the data analysis technique used multiple linear regression analysis . Findings: The results of the study indicate that the hypothesis in this study is accepted, both partially (alone) and simultaneously (together). The results of the first test obtained a sig. value of 0.047 <0.05 and a t-count value of 2.011> t-table 1.989. This indicates that Ha1 is accepted; there is an influence of ISMUBA teacher pedagogical competence on the instillation of Islamic religious values in students of SMP Muhammadiyah Al Mujahidin Gunungkidul. The results of the second test obtained a sig. value of 0.033 <0.05 and a t-count value of 2.161> t-table 1.989. These results indicate that Ha2 is accepted; there is an influence of ISMUBA teacher professional competence on the instillation of Islamic religious values in students of SMP Muhammadiyah Al Mujahidin Gunungkidul. The results of the third test obtained a sig. value of 0.000 <0.05 and an F-count value of 12.937> F-table 3.09. These results indicate that Ha3 is accepted; there is an influence of the pedagogical and professional competence of ISMUBA teachers on the instillation of Islamic religious values in students of SMP Muhammadiyah Al Mujahidin Gunungkidul. The coefficient of determination R = 0.220 = 22%. These results indicate that the independent variables, namely pedagogical competence and professional competence of ISMUBA teachers, together influence the dependent variable, namely the instillation of Islamic religious values in students by 22%. Research implications/limitations: This study can generally provide an overview of teacher competence in pedagogical and professional aspects. More specifically, this study can be a simple reference in research on Ismuba in Muhammadiyah schools at the junior high school level. Originality/value: this study is the result obtained from field research and has a novel value in the context of competence for Ismuba teachers at the junior high school level. Further research can develop more widely both in terms of methodology, subjects and scope of the research area